The application of interior designing in the advancement of low-cost housing - Benitez, Kristine December O.; Mayo, Adelaida Villaraza (1998.)
(no abstract provided by the author)
Thesis(BID)--University of the Philippines Diliman.
Keywords: Housing; Interior decoration